The study of risk factors that lead to road accidents among students In Heal Th Campus Universiti Sains Malaysia - Zuladzhar, Nur Ainn (Universiti Sains Malaysia, 2016)
The rate of road accidents are increasingly worried. The aim of this research was to study the risk factors that can lead to road accidents among students in Health Campus Universiti Sains Malaysia. The specific objectives for this study were to determine the relationship between gender, attitude and behavior with road accidents. The study was conducted among 162 students at School of Health Sciences Universiti Sains Malaysia. The instrument used in this research to fulfill the objectives of the study was Questionnaire form. The Questionnaire consists of section A (demographic data), section B (behavior) and section C (attitude). A Chi Square test and Spearman’s Correlation test were used to answer the objectives of the study. The finding showed that there were no significant relationship between gender (p= 0.217), attitude (p- 0.143) and behavior (p= 0.838) with road accidents. Overall, the risk factors of road accidents among students in Health Campus Universiti Sains Malaysia does not lead to road accidents.